Nitrogen and Oxygen Gas Isotopes in the Siple Dome and Byrd Ice Cores, Antarctica - Severinghaus, Jeffrey P. (IEDA: US Antarctic Program Data Center, 2009)
This data set consists of Gas-isotopic data from the Siple Dome and and Greenland Ice Sheet Project 2 (GISP2) ice cores covering roughly the last 100,000 years (100 ka), consisting of d15N (15N/14N) of N2, d18O (18O/16O) of O2, dO2/N2, and dAr/N2. Derived parameters include d18Oatm, d15N, dO2/N2, and dAr/N2. Data are available via FTP as ASCII text files (.txt) and Microsoft Excel files (.xls).